NATIONAL HOLIDAYS AROUND THE WORLD - Keldieva Sohiba Khayitmurodovna (Bright Mind Publishing, 2025)
This article explores the significance and diversity of national holidays across different countries. It examines how historical events, cultural traditions, and national identity shape these celebrations. The study highlights notable examples from around the world, comparing customs, rituals, and social practices. By understanding national holidays, we gain insight into the values, heritage, and collective memory of different societies.
Keywords: National holidays, cultural traditions, history, celebrations, customs, rituals, national identity, global diversity.